PENGARUH KUALITAS LAYANAN DAN CITRA MERK TERHADAP LOYALITAS MELALUI KEPUTUSAN PEMBELIAN NASABAH PEGADAIAN DI KANWIL XII SURABAYA - Pisesha, Paramitha Agil (Prodi Magister Manajemen Universitas Wijaya Putra, 2025)
The aim of this research is to test and analyze the influence of service quality and brand image on loyalty both directly and through purchasing decisions of Pegadaian customers at Kanwil XII Surabaya. The research method uses descriptive research with a quantitative approach. This research utilized Nonprobability Sampling sampling techniques with a total of 210 respondents and used data analysis with the SEM-PLS (Structural Equation Modeling- Partial Least Square) Outer Model and Inner Model techniques. The results of the research analysis show that 1) Service quality has a significant positive influence on purchasing decisions of Pegadaian customers. 2) Brand Image has a significant positive influence on Purchase Decisions of Pegadaian Customers. 3) Service quality has a significant positive influence on Pegadaian Customer Loyalty. 4) Brand Image has no influence on Pegadaian Customer Loyalty. 5) Purchasing decisions have a significant positive influence on Pegadaian customer loyalty. 6) Service quality has a significant positive influence on Pegadaian customer loyalty through purchasing decisions. 7) Brand image has a significant positive influence on Pegadaian customer loyalty through purchasing decisions.